Manejo integral de la eclampsia: análisis de un caso clínico. - Moreira Macías, Melisa Merlyn; Rueda Romero, Monica Mishelle (My University, 2024)
Hypertensive disorders of pregnancy (HDP), particularly eclampsia, are among the leading causes of maternal and perinatal morbidity and mortality worldwide. In Ecuador, preeclampsia significantly affects a considerable percentage of pregnant women, constituting a public health concern. Eclampsia, characterized by seizures not attributable to other causes in women with preeclampsia, requires immediate and multidisciplinary intervention. To develop a nursing care plan for a patient diagnosed with eclampsia, applying the Nursing Process (NP) based on Marjory Gordon’s functional health patterns and the NANDA-I, NOC, and NIC taxonomies. A 22-year-old primigravida at 32 weeks of gestation was admitted unconscious after experiencing generalized tonic-clonic seizures and a blood pressure of 170/114 mmHg. She underwent intubation, sedation, administration of magnesium sulfate and antihypertensives, and emergency cesarean delivery, resulting in a live preterm newborn. A basic descriptive qualitative study with a case study design was conducted. Data collection involved direct observation, interviews, and medical record review. Alterations were identified in the cognitive perceptual, activity-exercise, nutritional-metabolic, and role-relationship patterns. Nursing diagnoses included risk for unstable blood pressure and impaired maternal-fetal dyad. Interventions focused on hemodynamic stabilization, seizure prevention, fluid management, psychosocial support, and discharge education. The structured implementation of the Nursing Process enabled comprehensive, safe, and effective care. The nursing approach played a critical role in achieving maternal stabilization and neonatal well-being, reaffirming its essential function in managing obstetric emergencies.
La eclampsia, representa una de las principales causas de morbimortalidad materna y perinatal a nivel global. Afecta a un importante porcentaje de gestantes, siendo un problema de salud pública. Su cuadro clínico se caracteriza por convulsiones no atribuibles a otras causas en mujeres con preeclampsia. Desarrollar un plan de cuidados de atención de enfermería, basado en los patrones funcionales de Marjory Gordon. La metodología aplicada análisis de estudio de caso clínico. Mediante la observación directa, entrevistas y como instrumento de recolección de datos se hizo uso de historia clínica. El presente estudio se lo realizo en un Hospital General de la Ciudad de Machala, en una madre primigesta de 22 años, con embarazo de 32 semanas de gestación, es ingresada al área de cuidados intensivos con Glasgow de 3/15, al ingreso presenta convulsiones tónico-clónicas, presión arterial de 170/114 mmHg, se realiza cesárea de emergencia obteniendo producto único vivo con prematurez moderada, se transfiere a Unidad de cuidados intensivos neonatal donde permanece por un mes. Se identificaron alteraciones en los patrones funcionales cognitivo-perceptual, actividad-ejercicio, nutricional-metabólico. La aplicación del PAE permitió una atención efectiva contribuyendo a la estabilización materna y al bienestar neonatal reafirmando así el papel fundamental del personal de enfermería en la atención de emergencias obstétricas.
Keywords: ECLAMPSIA; PROCESO DE ENFERMERÍA; CUIDADOS DE ENFERMERÍA